1979
DOI: 10.1177/106002807901300301
|View full text |Cite
|
Sign up to set email alerts
|

Drug Compliance — A Study of Patient Behavior Based on Medical Records

Abstract: Studies concerned with medication compliance after initial prescription dispensing have been frequently cited in the literature; however, little research has been done on the initial filling of the prescription order. In order to ascertain the degree of compliance at the initial filling level, a study was carried out on a population associated with a neighborhood health center. Overall, the study indicated an initial filling compliance of 94 percent, which was affected by the site of patient encounter, the chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A critical first step to studying medication adherence is assessing whether the patient filled the prescription. While most studies have focused on adult patients, 2 studies included children and found that prescriptions for medications for chronic illnesses 3 and for younger patients 4 were more likely to be filled.…”
mentioning
confidence: 99%
“…A critical first step to studying medication adherence is assessing whether the patient filled the prescription. While most studies have focused on adult patients, 2 studies included children and found that prescriptions for medications for chronic illnesses 3 and for younger patients 4 were more likely to be filled.…”
mentioning
confidence: 99%
“…This study examines level I compliance (Luckman et al, 1979) for patients in the dispensed group but not necessarily for those in the prescription group. However, Widmer has contended that level I compliance implies level 11 compliance because patients would not continue to purchase medications (either by returning for dispensed drugs or by refilling prescriptions) unless they were taking them (Widmer, Cadoret, & Troughton, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The filling of a prescription has been referred to as level I compliance and the actual taking of the medication as level I1 compliance (Luckman et al, 1979). Prescriptions for acute medications, ease of access to a pharmacy, and frequent doctor-patient interaction tend to increase compliance (Luckman,et al, 1979). For the patient on chronic medication, physician dispensing should provide both easy access and increased interaction and, therefore, should foster compliance.…”
mentioning
confidence: 99%
“…Student's two‐tailed t ‐test was used for analysis of continuous numerical variables. The χ 2 test was used for analysis of categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…Compliance has been subclassified into: primary compliance, the filling of prescriptions; and secondary compliance, the taking of prescribed medication obtained 2 . Paediatric patients depend on a carer to fill the prescription and to administer medication.…”
mentioning
confidence: 99%